Tumor Diagnosis: Discovering of Tumor‐targeting Peptides using Bi‐functional Microarray (Adv. Healthcare Mater. 18/2015). Issue 18 (December 2015) - Wang, Weizhi; Wang, Zihua; Bu, Xiangli; Li, Ren; Zhou, Mingxing; Hu, Zhiyuan
Abstract : A silicon based bi‐functional microwell array for both in situ peptide sequencing and fluorogenic detection is presented. On page 2802, W. Wang, Z. Hu, and co‐workers show how positive hits from high throughput peptide library can be screened out efficiently through the direct reading of the fluorescence and single‐bead MS sequencing. Novel peptides with nanomolar affinities and high specificities towards tumor marker are obtained.